Aksi Pengembara (Pemuda Penggagas Pembaruan) Umsida Students to Help Manage Used Cooking Oil in Klurak Village Rw 07 - Shinta Anastasya Putri; Ainur Rochmania; Poppy Febriana; Nabila Ayu Bakhta; Ramadhani Putra (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Humans have a variety of activities that support the increasing amount of waste in the community environment. One of the household wastes produced is waste oil or what is often referred to as used cooking oil. Waste oil can be categorized as used cooking oil when it changes color to blackish brown. Discolored waste oil is no longer suitable for consumption. Some people with limited information about used cooking oil processing, tend to throw it away and result in environmental pollution. There are also many people who do not care about the impact of littering used waste. This dedication through Action Nomads is carried out to educate the people of Klurak Village RW 07 in raising awareness about the impact of waste used waste disposal and how to improve skills in managing used cooking oil. As for empowering youth who will later continue the Nomad Action in caring for the environment from the dangers of waste cooking oil in the surrounding environment. The method used in this study is by outreach to the community about the use value of used cooking oil waste which can produce a useful and valuable product. As youths, the servant collaborated with youth youth organizations in Klurak Rw 07 Village to campaign for a movement to reduce the use of used cooking oil. The result of implementing this activity is increasing knowledge about the impact of waste used cooking oil and using this used cooking oil to be used as a material that is ready for reuse.